Unplugged - MacKenzie, Brian, 1974- (Victory Belt Publishing, 2017)
We're looking at our wrists not only to check the time, but also to see how much we've moved, monitor our heart rate, and see how we're stacking up against yesterday's tallies. By 2020, the global market for fitness-focused apps and devices is expected to grow to $30 billion. The authors believe we are turning rich experience into yet another task we need to complete to meet our daily goals. They encourage you to reconnect to your instincts and the natural world, and avoid the common mistakes that most people make with wearables and tracking apps.